Benign adenomyoepitelioma of the breast: Presentation of two rare cases and review of literature. (2020) - Intagliata, Eva; Gangi, Santi; Trovato, Claudio; Vecchio, Rosario; Strazzanti, Angela
Highlights: Adenomyoepithelioma of the breast is a rare benign breast neoplasm. The rarity of this histological type of benign breast tumor and the finding of two cases in a short period makes this case report unique. Although benign, adenomyoepithelioma has a potential for local recurrence; therefore, wide excision is recommended. Abstract: Introduction: Adenomyoepithelioma of the breast is a rare benign breast neoplasm with a particular behaviour. Presentation of cases: We report two cases of adenomyoepithelioma of the breast in two old female patients, diagnosed over a period of 5 years. The clinical presentation, the radiological and the histopathologic findings are discussed. Discussion: Adenomyoepithelioma of the breast is characterized by the proliferation of both epithelial and myoepithelial cells belonging to the breast lobules and ducts. The imaging features are not pathognomonic and FNAB is usually not diagnostic. The morphologic appearance of this tumor varies, and it has to be considered in the differential diagnosis with other breast tumors. Although benign, adenomyoepithelioma has a potential for local recurrence, and malignant transformation is possible; therefore, wide excision is recommended to lower the recurrence rate. Conclusion: The rarity of this histological type and the finding of two cases in a relatively short period makes this case report unique.